Perbandingan Model Pembelajaran Kooperatif Think Pair Square (Tps) Dengan Student Team Achievment Divission (Stad) Untuk Meningkatkan Kemampuan Komunikasi Matematika Siswa Pada Pokok Bahasan Himpunan - Saraswati, Dewi (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2013)
The comparison between cooperative learning Think Pair Square (TPS) and Student Team Achievement Divissions (STAD) for improving Mathematics communication ability of Junior High school.The main purpose of this study was (1) to know difference between student who received cooperative learning Think Pair Square (TPS) and Student Team Achievement Divissions (STAD) (2) how mathematic communication ability students who learned with cooperative learning Think Pair Square (TPS) and Student Team Achievement Divissions (STAD)? which cooperative learning Think Pair Square (TPS) and Student Team Achievement Divissions (STAD) better for improving mathematic communication ability. This research is a form of experimental studies pre-test and post-test control group design. Research subjects grade VII A who received cooperative learning Think Pair Square (TPS) and grade VII B who received Student Team Achievement Divissions (STAD).The data was collected using a test instrument of the mathematical communication ability, attitude scales, and observation sheet. The results obtained are: 1) there are diference between student who received cooperative learning Think Pair Square (TPS) and Student Team Achievement Divissions (STAD) (2) mathematical communication ability of student receiving TPS type of cooperative learning Think Pair Square (TPS) better than student who receiving Student Team Achievement Divissions (STAD).(3) improving mathematical communication ability of students receiving TPS type of cooperative learning better than student who receiving Student Team Achievement Divissions (STAD)